STUDI EMPIRIS WIRAUSAHA PEREMPUAN DI SURAKARTA : FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI, HAMBATAN DAN KEBERHASILAN USAHA - Prasetyani, Dwi; Purusa, Nanda; Hasbianto, Indra (Universitas Dian Nuswantoro Semarang, 2016)
The role of women entrepreneurs has been growing and contributing significantly to economic growth. However, understanding common problems and success factors can help women entrepreneurs in developing their business. Many women entrepreneurs have begun to experience problems, which due to socio-economic factor. This research examines factors affecting motivation, obstacle, and success of women entrepreneurs in Surakarta. Data was collected using a self administered questionnaire that was distributed directly to women entrepreneurs, therefore goodness of data determined through reliability test and validity test. Linear regression analysis was used as a more suitable methodology to identify the important determinants of motivation, obstacles, success of women entrepreneurs. The result shows that level of education significanly affects women's entrepreneurial motivation and obstacles which they have to face. The existence of social relationship positively influences both in motivations and business success. On the other hand family supports only affect on business success of women entrepreneurs.Keywords:Â Women Entrepreneur; Motivation; Obstacle; Success